Psychosocial Effects of the COVID-19 Pandemic on Patients With Schizophrenia and Their Caregivers - Alejandra Caqueo-Urízar (Frontiers Media S.A., 2021)
The aim of this study was to analyze the psychosocial effects of the COVID-19 pandemic on 120 patients with schizophrenia, and their caregivers (control group), in the city of Arica, northern Chile. The hypotheses of this study hold that (1) self-reports of the impact of the COVID-19 pandemic among patients and caregivers would be positively correlated, (2) caregivers would self-report a greater impact of the pandemic on their daily lives, and (3) patients infected with COVID-19 would experience lower levels of mental health improvement and higher levels of psychological distress. Hypotheses were tested using correlations, mean differences, and effect sizes (Cohen’s d). The results showed that patients with schizophrenia who had been in quarantine for almost a year showed similar levels of concern as their caregivers in the domains of health and social life. However, caregivers showed significant differences from patients in the areas of income, concern, and employment status. In addition, patients who were infected with COVID-19 showed lower levels of well-being and worse psychological recovery. The implications of the findings highlight the need to incorporate mental health interventions in the pandemic health context for caregivers of people with schizophrenia. Finally, the results suggest that Covid-19 infection has a significant effect on the recovery and psychological well-being of patients with schizophrenia.